Genetic Variability, Character Association, and Path Analysis for Economic Traits in Menthofuran Rich Half-Sib Seed Progeny of Mentha piperita L. (22nd May 2014) - Kumar, Birendra; Mali, Himanshi; Gupta, Ekta
Abstract : Menthofuran rich eight half-sib seed progeny of Mentha piperita (MPS-36) were studied for various genetic parameters, namely, coefficient of variation, heritability, genetic advance, correlation, and path of various plant and oil attributes, namely, plant height, L : S ratio, herb yield, β -myrcene, limonene, 1, 8-cineole, menthone, menthofuran, neomenthone, pulegone, and menthol. Maximum genotypic coefficient of variation and genetic advance as percentage of mean were recorded for pulegone, followed by menthofuran and 1, 8-cineole. The genotypic correlation in general was higher than phenotypic; positive significant correlation was recorded for limonene with 1, 8-cineole and menthone, β -myrcene with limonene, and 1, 8-cineole and menthofuran with neomenthol. A high direct positive effect on menthofuran was of neomenthol.